Desenho e validação de um instrumento de compreensão do tempo histórico em alunos do ensino medio - Carrillo Cayllahua, Javier (2022)
The objective of the research is to design and validate an instrument for the evaluation of the understanding of historical time in high school students, based on the Critical Theory of History and based on the proposal of a theoretical model of historical time, which includes eight temporal concepts: 1) Chronology, 2) Periodization, 3) Succession, 4) Causality, 5) Duration, 6) Simultaneity, 7) Change 8) Continuity. The results of the validation and reliability of the instrument called Questionnaire on the understanding of historical time in high school students are presented. Validation was done through item - test correlation in a sample of 302 students, and the validity coefficient was established using Pearson's product moment formula. Reliability was obtained through the test - re test, applied to a sample of 100 students; establishing the reliability coefficient by means of the Pearson r formula and Student's t. It is concluded that the questionnaire has validity and reliability, so it is an instrument that allows evaluating the understanding of historical time as a mega-concept that integrates a set of temporal concepts of history.